DIRTY AIR FILTER SYSTEM USING BOXED EQUALIZER MQ-8 AND MQ-9 WHEELED ROBOT - Anggara Trisna Nugraha (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2018)
Air is the layer of gas that envelopes the Earth. Clean air is air free of pollutants or substances that can poison the body and are commonly found in areas with many plants. Thus, the result of carbon monoxide emissions that have been processed will produce oxygen gas because the steel plate on the Box Analizer serves as a carbon element binder. This applied model does not change the shape of the vehicle so that the vehicle is able to process the carbon monoxide gas outside the system. In this test is used smoke from paper burning to provide action on the sensor. The amount of smoke which is the form of output already in the form of ppm (part per million) can be known by using the display on the serial monitor and with calibration using a gas analyzer. Gas analyzers are in the lowest range of 120ppm detecting sensors of 116ppm with a percent error of 17%.DOI : https://doi.org/10.26905/jeemecs.v1i1.2301